Comparing Torque Loss in Standard Implants and Short Implants with Increased Vertical Cantilever Abutments: an In Vitro Study - Jalalian, Ezzatollah; Yousofi, Zahra (Brazilian Dental Science, 2020)
Objectives: With regard to the prevalence of abutment screw loosening (SL) and bone height reduction, particularly in the posterior regions of the jaws, as well as the contradictory issue of applying short implants instead of surgeries, along with all preparations associated with longer implants, the present study aimed to compare the amount of torque loss in short implants with increased vertical cantilever abutments and standard ones. Material and Methods: In this experimental study, a total number of 20 implants (MegaGen Implant Co., Ltd, South Korea) with 4.5 mm diameter including 10 short implants (7 mm) and 10 standard ones (10 mm) were utilized. Using a surveyor, fixtures were perpendicularly mounted in 13×34 mm resin for short implants and 19×34 mm resin for standard ones. The abutments of the same height but different cuff heights (2.5 mm for the standard implants and 5.5 mm for the short ones) were then tightened with 30 N.cm, via a digital torque meter. To compensate the settling effect, the abutment screw was re-tightened with 30 N.cm after 10 min. Upon applying 500,000 cycles at 75 N.cm and 1 Hz along the longitudinal axis on each sample, blind reverse torque value (RTV) was measured with a digital torque meter. The data were finally analyzed using Student’s t-test. Results: Both groups experienced torque loss, but there was no statistically significant difference between the case and control groups in terms of abutment SL (p = 0451). Conclusion: Short implants seem to be a good mechanical alternative in emergencies with respect to torque loss and abutment SL. KEYWORDS Reverse torque value; Cyclic loading, Short implant; Screw loosening; Crown-implant ratio; Torque loss.